Progressive symmetric eritrocarotodermia Gottron: A rare case - M. M. Tlish; N. L. Sycheva; N. A. Boyko; M. E. Shavilova; F. A. Psavok (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
The article deals with ethiopathogenetic factors of origin of progredient symmetric erythrokeratodermia of Gottron which is mainly characterized by autosomal dominant mode of inheritance and is classified as a disorder of cornification with extra epidermal cellular proliferation.Clinicopathologic criteria on the basis of which this pathology can be verified are described here, such as: onset of a disease at an early age, strictly divided polycyclic, fixed, hyperkeratotic plaques with a narrow erythematic crown and a clean-cut, sometimes hyper pigmented edge, which are symmetrically located on skin on head, buttocks, limbs and are not prone to quick peripheral growth; large frequency of palmoplantar keratoderma and also histological changes typical of erythrokeratodermia.The article describes a rare clinical case of autosomal-recessive progredient symmetric erythrokeratodermia of Gottron which is distinguished by seasonal changes of skin pathological process - emergence of rash in winter and complete remissions in summer.